Effectiveness of the Graphical Formation in the Prophetic Hadith - Tavga Jasm Muhammad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
This study is an academic attempt entitled (Effectiveness of the graphical formation in the Prophetic Hadith) that seeks to show the aesthetics of the hadiths of the Prophet in an artistic perspective, so that makes the Prophetic Hadiths the starting point. The research consists of two chapters preceded by a preface and followed by results. As for the preface, it deals with the concept of formation and statement, as well as talking about the eloquence of the prophetic statement, followed by the preliminary three study axes on me the first axis with analogous formations, while the second axis came to talk about metaphor formations, and the third axis of it is devoted to the hadith on metamorphic formations, and axes tracking are a conclusion that summarizes the most prominent search results.